PERAN BALI DEMOCRACY FORUM (BDF) DALAM DEMOKRASI INDONESIA - , FUAT ALBAYUMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of democracy in Indonesia is strongly influenced by external factor. In according to filter Indonesia democracy from external bad influence, Indonesia introduced Bali Democracy Forum in 2008. As is goes to the 6th in 2013, BDF proved be strengthen Indonesian Democracy by its role as Asia-Pacific diplomatic forum to support democracy, as learningship media for homegrown democracy in that area, and promotion media to show Indonesia as democratic state.